BATF Potentially Mediates Negative Regulation of PD-1/PD-Ls Pathway on T Cell Functions in Mycobacterium tuberculosis Infection - Liu, Qianqian; Ou, Qinfang; Shen, Lei; Qiu, Chao; Zhang, Bingyan; Zhang, Wenhong; Shao, Lingyun; Gao, Yan; Chen, Zheng W. (Frontiers in Immunology, 2019)
Background: Previously, we have found that blockade of PD-1/PD-Ls pathway could enhance CD4+ T cells-mediated protective immunity in patients with active tuberculosis (ATB). However, the mechanism of PD-1/PD-Ls pathway involved in negative regulation of anti-TB immunity has been still unclear. Recently, the study of human immunodeficiency virus (HIV) infection demonstrated that PD-1 could induce the expression of basic leucine zipper ATF-like transcription factor (BATF) to inhibit CD8+ T cell function. While the mechanism of immune regulation of BATF in Mycobacterium tuberculosis (M. tb) infection has not yet been elucidated. Methods: We enrolled 104 participants including ATB patients (n=66), latent tuberculosis infection (LTBI) (n=16) and healthy control (HC) (n=22). The expressions of BATF in peripheral blood CD4+ and CD8+ T cells from enrolled subjects were determined using flow cytometry. Intervention with PD-1/PD-Ls pathway was performed by using blocking antibodies or human PD-L1 fusion protein. Silencing BATF in peripheral blood mononuclear cells (PBMCs) by electroporation with siRNA. Real-time quantitative PCR, CFSE dilution assay and enzyme linked immunosorbent assay (ELISA) were employed to test T cell functions after BATF knockdown. Results: The percentages of BATF+CD4+ (P=0.0003 and P<0.0001, respectively) and BATF+CD8+ (P=0.0003 and P=0.0003, respectively) cells were significantly increased in ATB patients compared with LTBI and HC. BATF-expressing PD-1+ T cells in CD4+ and CD8+ T cells were much higher in ATB group than those in LTBI group (P=0.0426 and 0.0104, respectively) and HC group (P=0.0133 and 0.0340, respectively). There was a positive correlation between BATF expression and PD-1 expression in ATB patients (for CD4+ T cells, r=0.6761, P=0.0158; for CD8+ T cells, r=0.6104, P=0.0350). BATF knockdown could enhance IL-2 and IFN-γ secretions (P=0.0485 and 0.0473, respectively) and CD4+ T cells proliferation (P=0.0041) in vitro. Conclusions. In the context of tuberculosis, BATF mediates negative regulation of PD-1/PD-Ls pathway on T cell functions. BATF knockdown can improve cytokine secretion and cells proliferation in vitro.